2018
DOI: 10.1080/00332747.2017.1354622
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Perceived Discrimination With Impaired Functioning in a Population Sample With Psychological Distress

Abstract: Objective To test associations between perceived discrimination based on mental health status and impaired functioning in a population sample with psychological distress. Methods Interviews were conducted with a sample of respondents to the California Health Interview Survey with mild, moderate, or severe psychological distress. Perceived discrimination was assessed using 14 items covering four domains in which discrimination is reported: social, partner, institutional, and work. Associations of perceived di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Prior studies have established negative effects on mental health from perceive discrimination regardless of the reason for this discrimination. 21 Nonetheless, universities would benefit from knowing the source of this bias so they can address this behavior on their campuses.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have established negative effects on mental health from perceive discrimination regardless of the reason for this discrimination. 21 Nonetheless, universities would benefit from knowing the source of this bias so they can address this behavior on their campuses.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…17 Graduate students have reported discrimination as a result of their gender, 18 sexual orientation, 19 and race or ethnicity, 20 In one study, more than half of graduate students reported experiencing discrimination in their graduate program. 21 Regardless of the source of bias, perceived discrimination is related to high rates of distress. 22…”
mentioning
confidence: 99%
“…38,39 Culturally responsive clinical practices that remove barriers to accessing treatment, implement individualized care based on pa- tient need, and promote flexible services are crucial to the incorporation and inclusion of groups who have been underserved in mental health settings and are less likely to seek help in the first place. 40,41 Public health, community partnerships, and antistigma initiatives could help to bridge this gap through improved patient engagement efforts that promote and normalize help-seeking and service use for those contemplating mental health care. The high levels of MDD and the low levels of mental health treatment access may in part be attributed to COVID-19 restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of discrimination experienced by people with mental health problems is alarming given that it has been associated with a range of negative outcomes including reduced social capital and loneliness [8, 9], as well as impaired functioning (days out of role) and unemployment [10, 11]. There is also some evidence that discrimination may lead to reduced health service use [12, 13], and because of this, poorer clinical and personal recovery [14].…”
Section: Introductionmentioning
confidence: 99%